2014
DOI: 10.1016/j.humpath.2014.06.003
|View full text |Cite
|
Sign up to set email alerts
|

HRAS mutations are frequent in inverted urothelial neoplasms

Abstract: Inverted urothelial papilloma (IUP) is an uncommon neoplasm of the urinary bladder with distinct morphological features. Studies regarding the role of human papillomavirus (HPV) in the etiology of IUP have provided conflicting evidence of HPV infection. Additionally, little is known regarding the molecular alterations present in IUP or other urothelial neoplasms which might demonstrate inverted growth pattern like low-grade or high-grade urothelial carcinoma. Here, we evaluated for the presence of common drivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(51 citation statements)
references
References 34 publications
4
47
0
Order By: Relevance
“…Variants passing filtering in APCCs that were called as variants (regardless of filtering status) in any normal tissue were considered germ line/artifacts and excluded from additional analysis unless occurring at a previously reported residue associated with APA. These filtering criteria are more stringent than our previously validated criteria for calling single-nucleotide/indel variants from AmpliSeq data (41,43). All somatic APCC variants were visually confirmed in Integrative Genomics Viewer (Broad Institute), and paired normal samples were inspected in Integrative Genomics Viewer to confirm lack of substantial read support for the called variant.…”
Section: Methodsmentioning
confidence: 99%
“…Variants passing filtering in APCCs that were called as variants (regardless of filtering status) in any normal tissue were considered germ line/artifacts and excluded from additional analysis unless occurring at a previously reported residue associated with APA. These filtering criteria are more stringent than our previously validated criteria for calling single-nucleotide/indel variants from AmpliSeq data (41,43). All somatic APCC variants were visually confirmed in Integrative Genomics Viewer (Broad Institute), and paired normal samples were inspected in Integrative Genomics Viewer to confirm lack of substantial read support for the called variant.…”
Section: Methodsmentioning
confidence: 99%
“…Data analysis was performed essentially as described(12) in Torrent Suite 4.0.2, with alignment by TMAP using default parameters, and variant calling using the Torrent Variant Caller plugin (version 4.0-r76860) using default low-stringency somatic variant settings. Variants were annotated using Annovar(13).…”
Section: Methodsmentioning
confidence: 99%
“…However, HPV has not been detected through immunohistochemistry or in situ hybridization (ISH), which is more specific for HPV infection in tissues. 1,15 …”
Section: Etiologymentioning
confidence: 99%
“…This mutation is rarely seen in UC. 15 Telomere shortening is another useful biomarker in distinguishing IUP from UC. Williamson et al found a statistically significant reduction in the relative telomere length (RTL) in UC with inverted growth compared to those found in IUP.…”
Section: Distinguishing Iup From Ucmentioning
confidence: 99%